Arsenic polluted waters: Application of geochemical modelling as a tool to understand the release and fate of the pollutant in crystalline aquifers. (1st January 2022) - Fuoco, I.; De Rosa, R.; Barca, D.; Figoli, A.; Gabriele, B.; Apollaro, C.
Abstract: Arsenic (As) is one of the most investigated elements worldwide due to its negative impact on the natural system. Its geochemical behavior depends on several geogenic processes, which can cause hazardous enrichment into natural waters, even in remote areas, far from anthropogenic sources. In this work the arsenic pollution issue has been addressed by studying water-rock interaction processes and applying reaction path modelling as a tool to understand the rock-to-water release of As and the fate of this natural pollutant in crystalline aquifers. In-depth geochemical characterization of several water samples discharging from crystalline aquifers was performed. The obtained data were used to fix the boundary conditions and validate the modelling outcomes. The performed modelling allowed to reconstruct the water-rock interaction processes which occur (i) in shallow and relatively shallow crystalline aquifers in which no As anomalies were observed and (ii) in As-rich areas, coupling reaction path modelling of granite dissolution with adsorption of dissolved As onto precipitating crystalline and amorphous Fe(III)-oxyhydroxides given the widespread presence of these phases in the studied environment. The results of the geochemical modelling are in agreement with the analytical data and reproduce them satisfactorily. The performed geochemical modelling is of high environmental significance because it is a flexible and powerful tool that correctly defines the water-rock interaction processes occurring in crystalline aquifers, providing valuable data to improve the knowledge on As behavior, not only in the study area, but also in similar geological settings worldwide. Therefore, the present research has broad future perspectives in the environmental field. Graphical abstract: Image 1 Highlights: The reaction path modeling is a powerful tool to define the geochemical behavior of arsenic. Crystalline aquifers can contain high arsenic levels due to dissolution of As-rich phases. The pyrite dissolution depend on dissolved oxygen and on availability of Fe(III) in the water. The Fe(III)-oxyhydroxides at variable crystallinity control the dissolved As levels in groundwaters.